1993
DOI: 10.1152/jn.1993.70.1.167
|View full text |Cite
|
Sign up to set email alerts
|

Voltage dependence of the rat chorda tympani response to Na+ salts: implications for the functional organization of taste receptor cells

Abstract: 1. Voltage-clamp and current-clamp data were obtained from a circumscribed region of the anterior rat lingual epithelium while simultaneously monitoring the afferent, stimulus-evoked, neural response from the same receptive field. 2. Chorda tympani (CT) responses at constant Na(+)-salt concentration were enhanced by submucosa negative voltage clamp and suppressed by positive voltage clamp. The complete CT response profile, including the time course of adaptation, was not uniquely determined by NaCl concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
111
0
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(119 citation statements)
references
References 0 publications
6
111
0
2
Order By: Relevance
“…Together, these results suggest that rather than responding to sodium activation of the AS transduction pathway, the behavioral detectability of high NaGlu concentrations derives from some cue related to the gluconate anion or perhaps activation of the AI pathway due to leakage of sodium through tight junctions, or AI apical channels, as a result of the high Na ϩ concentration gradient. In summary, these data support Bernstein & Hennessy's (1987) conclusion that the AS sodium transduction pathway is necessary for sodium recognition in the rat, and furthermore strongly suggest that this pathway is also sufficient (see Elliot & Simon, 1990;Formaker & Hill, 1988;Ye et al, 1993). We have also extended previous studies of the effects of amiloride on salt appetite to show that the sodium specificity of the appetite is completely abolished when the AS pathway is blocked, coupled with a modest increase in appetitive behavior.…”
Section: Discussionsupporting
confidence: 85%
“…Together, these results suggest that rather than responding to sodium activation of the AS transduction pathway, the behavioral detectability of high NaGlu concentrations derives from some cue related to the gluconate anion or perhaps activation of the AI pathway due to leakage of sodium through tight junctions, or AI apical channels, as a result of the high Na ϩ concentration gradient. In summary, these data support Bernstein & Hennessy's (1987) conclusion that the AS sodium transduction pathway is necessary for sodium recognition in the rat, and furthermore strongly suggest that this pathway is also sufficient (see Elliot & Simon, 1990;Formaker & Hill, 1988;Ye et al, 1993). We have also extended previous studies of the effects of amiloride on salt appetite to show that the sodium specificity of the appetite is completely abolished when the AS pathway is blocked, coupled with a modest increase in appetitive behavior.…”
Section: Discussionsupporting
confidence: 85%
“…NaCl evokes a stronger saltiness than Na sulphate, for example. One explanation for this involves the ability of Na + to permeate deep into the taste bud by penetrating through the tight junction spaces at the apical tips of cells [48]. The apical tips of taste bud cells, as in all epithelial boundaries, are sealed by a junctional complex including the zonula occudens.…”
Section: Salty Chemosensory Transductionmentioning
confidence: 99%
“…Thus, in contrast to the predictions based on CT recordings, discrimination in all four strains appeared to depend on the amiloride-sensitive transduction pathway, which, in the case of BALB/cByJ, 129P3/J, and DBA/2J (and perhaps C57BL/6 as well), may exist in taste buds innervated by nerves other than the CT. animal psychophysics; taste transduction; taste coding; C57BL/6; BALB/c; 129P3/J; DBA/2 THE TASTE OF SODIUM CHLORIDE appears to be transduced via at least two mechanisms, one which is selective for Na ϩ (and Li ϩ ) and is disrupted by the lingual application of the epithelial Na ϩ channel-blocker amiloride (e.g., Refs. 1,3,5,8,12,16,27, 39), and the other(s) which is amiloride-insensitive and cation nonselective (e.g., 12,17,20,22,30,[35][36][37]. In rats, electrophysiological recordings from the chorda tympani (CT) nerve have demonstrated that, when amiloride is applied to the lingual epithelium, the responsiveness of this nerve to sodium salts, but not to nonsodium salts, is markedly suppressed (e.g., Refs.…”
mentioning
confidence: 99%